Urnas y quioscos: dos espejos discordantes. - Bezunartea, Ofa (Estudios sobre el Mensaje Periodístico, 2000)
Ballot boxes and news stands: two discordant mirrors Who reflects more clearly the Basque Society, the press consumtion preferences or the electoral results? This article stems from the field research performed by the authors. They verified a paradox observed in the Basque country: the prevailing ideology is nationalist, however, the more widespread newspapers offer an ideology opposed to nationalism. 109 Ofa Bezunartea y Mercedes del Hoyo Urnas y quioscos: dos espejos discordantes Besides, the newspapers rates of reading are rather high in Euzkadi. It all turned out differently from what we had expected from the myth of the influence of the media. Likely explanations are offered in the conclusions of the article.